In vitro expression of the recombinant fusion protein of Newcastle disease virus from local Indonesian isolates by using a cell-free protein expression system - Aris Haryanto; Hevi Wihadmadyatami; Nastiti Wijayanti (Indonesian Journal of Biotechnology, 2020)
The aim of this work was the in vitro expression of the recombinant fusion (F) protein of Newcastle disease virus (NDV).  The pBT7-N-His-Fusion-NDV expression plasmid which carries the recombinant F protein encoding gene from local Indonesian isolates, was prepared and transformed into E. coli BL21 (DE3). To detect bacterial colonies carrying the recombinant plasmid, a restriction endonuclease analysis was performed using the EcoRI restriction endonuclease. These results showed that the pBT-N-His-Fusion-NDV plasmid was successfully isolated with a size of 4.601 bp, and three recombinant plasmids carrying the gene coding for the recombinant F protein of NDV were obtained. Selected recombinant plasmids were then in vitro by using a cell-free protein expression system followed by visualization of the recombinant F protein on a 12% SDS-PAGE gel both by Coomassie Brilliant Blue staining and Western blotting. Recombinant F protein was successfully in vitro expressed by using a cell-free protein expression system as indicated by a specific single protein band with a molecular mass of 25.6 kDa.